2002
DOI: 10.1161/01.cir.0000012544.07696.1f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3 Months of Antimicrobial Treatment With Clarithromycin in Acute Non–Q-Wave Coronary Syndrome

Abstract: Background-Coronary artery disease, an inflammatory disease, may be caused by infection. We investigated whether the antibiotic clarithromycin would reduce morbidity and mortality in patients with acute non-Q-wave coronary syndrome. Methods and Results-Altogether, 148 patients with acute non-Q-wave infarction or unstable angina were randomly assigned to receive double-blind treatment with either clarithromycin or placebo for 3 months. The primary end point was a composite of death, myocardial infarction, or un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 26 publications
2
75
0
4
Order By: Relevance
“…Trial populations were slightly variable. Six trials were conducted among patients with stable coronary artery disease (10,(13)(14)(15)(16)(17) and six trials involved patients with acute coronary syndromes (18)(19)(20)(21)(22)(23). The remaining trial was conducted among patients scheduled to undergo coronary artery bypass graft surgery (24).…”
Section: Resultsmentioning
confidence: 99%
“…Trial populations were slightly variable. Six trials were conducted among patients with stable coronary artery disease (10,(13)(14)(15)(16)(17) and six trials involved patients with acute coronary syndromes (18)(19)(20)(21)(22)(23). The remaining trial was conducted among patients scheduled to undergo coronary artery bypass graft surgery (24).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the recently published CLARIFY trial observed a reduction of the risk of ischemic cardiovascular events in patients presenting with acute non-Q-wave infarction or unstable angina attributable to clarithromycin treatment for 3 months. 10 B-mode ultrasonography provides the opportunity to relate risk factors to atherosclerosis in patients with early lesions. Ultrasonographically determined increased IMT of the CCA was identified as a strong predictor of stroke and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for Cp as a potential causative agent is strong and is based on findings of seroepidemiological studies, 5 in vitro animal models, 6 and pilot antichlamydial antibiotic intervention trials. [7][8][9][10][11][12] However, other clinical, 13,14 experimental, 15 and histopathological examinations 16 questioned the causal role of Cp for the development of atherosclerosis. Based on these different results, some investigators 14 hypothesize that the detection of a positive effect of antibiotic therapy on clinical end points may need even larger patient numbers or longer follow-up periods and that it therefore seems reasonable to analyze the impact of antibiotic therapy on surrogate parameters of atherosclerosis formation.…”
mentioning
confidence: 99%
“…This possibility is supported not only by the present study and the ROXIS study 9 but also by a recently published trial of clarithromycin in acute non-Q-wave coronary syndromes. 16 The design of the present study was pragmatic in ascertaining antibiotic efficacy but does not allow the drawing of conclusions as to the mechanism of action of these agents. The antibiotic regimens were chosen to represent a standard H pylori eradication course and a C pneumoniae treatment regimen.…”
Section: Discussionmentioning
confidence: 99%